Quality efficiency indicators of pharmacy management: characteristics, current features, opportunities and threats of the development - Iryna Volodimirivna Pestun (Journal of Global Pharma Technology, 2020)
The purpose of this work is a comprehensive research, analytical study and systematization of the pharmacies` management (networks) feature and trends in Ukraine in accordance with qualitative criteria. The objective is to determine the features and possibilities of improving the quality of pharmacies' management (networks), existing threats (risks) of their achievement, which allowed to highlight the topical issues and directions of the decision in the management of pharmacies and their networks. On the bases of scientific literature, regulatory documents, statistical data, information sites of the Internet and structural-logical, analytical methods, generalization, comparison, grouping, and formalization of reasoning were identified problems and trends in this area. The main groups of qualitative criteria for the pharmacies’ (networks) management effectiveness are: provision of pharmacy (network) management process; managerial decisions making; customer service; social management efficiency; the personality of the head; work with personnel. According to the results of the research, individual differences in ensuring the effective management of pharmacies and their associations (networks) are highlighted. It is shown that qualitative indicators of effective management of pharmacies (networks) are characterized by their dependence on the social and economic processes in society, changes in legislation, state and change of health protection, implementation of government social programmes, market and pharmacies informatization, consumer attitudes to treatment and their solvency, etc.Keywords: Pharmacies, Qualitative criteria of management efficiency, Possibilities of strengthening the management efficiency qualitative criteria, Threats.